2019
DOI: 10.22543/7674.61.p150156
|View full text |Cite
|
Sign up to set email alerts
|

Early Maladjustment Schemas in Individuals with and without Type 2 Diabetes Mellitus

Abstract: Objective. This study explored Early Maladjustment Schemas (EMSs) among individuals with and without type 2 diabetes mellitus and examined potential moderating roles for gender, level of education, and occupation.Methods. The sample included 371 adult participants (120 patients with diabetes and 251 individuals without diabetes), from Shiraz City, Fars province; Iran. The Young Schema Questionnaire-Short Form (YSQ-SF) was used to assess early maladjustment schemas.Results. Findings showed that patients with ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Mirdrikvand et al 20 compared EMSs between patients with and without T2DM; they found that abandonment, failure, vulnerability, F I G U R E 1 Demographic data of the participants. enmeshment, self-sacrifice, entitlement, and insufficient self-control schemas as well as the over-vigilance and inhibition schematic domains are higher in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Mirdrikvand et al 20 compared EMSs between patients with and without T2DM; they found that abandonment, failure, vulnerability, F I G U R E 1 Demographic data of the participants. enmeshment, self-sacrifice, entitlement, and insufficient self-control schemas as well as the over-vigilance and inhibition schematic domains are higher in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…(25) Maladaptive cognitive patterns from childhood and unmet basic needs are correlated with a general propensity for psychosomatic illness. (26) Regarding diabetes and cognitive patterns, the results of a study (27) showed that patients with type 2 diabetes have significantly higher scores on some cognitive patterns such as: abandonment, failure, vulnerability, self-sacrifice than the control group.…”
Section: Introductionmentioning
confidence: 99%